Characteristics Of Organizational Culture, Adaptation Ability, And Performance Of Micro, Small And Medium Enterprises - Muh. Husriadi; La Ode Agus Said; Bunga Kartika; La Ode Ahmad Darwin (Nomico, 2024)
This study investigates the role of organizational culture, adaptability, and performance of micro, small, and medium enterprises (MSMEs) in facing market dynamics and technological developments. Micro, Small, and Medium Enterprises (MSMEs) have a very important role in the economy, but often experience challenges in the adaptation process due to the lack of support from the right organizational culture. This study aims to explore the characteristics of organizational culture and adaptability in improving the performance of Micro, Small, and Medium Enterprises (MSMEs). The results of the study show that an organizational culture that supports adaptation and innovation can significantly improve the performance of micro, small and medium enterprises (MSMEs). The ability to adapt helps MSMEs respond to change and strengthens an organizational culture that is sensitive to needs. The results of this study indicate that the Micro, Small, and Medium Enterprises (MSMEs) sector needs to implement an adaptive organizational culture to increase competitiveness and ensure survival in an ever-changing market.